Bacterial Treatment and Metal Characterization of Biomedical Waste Ash. (13th August 2014) - Heera, Shelly; Kunal,; Rajor, Anita
Abstract : Biomedical waste ash generated due to the incineration of biomedical waste contains large amounts of heavy metals and polycyclic aromatic hydrocarbons (PAHs), which is disposed of in regular landfills, and results in unfavorable amounts of hazardous materials seeping into the ground and may pollute surface water and groundwater. Therefore, it is essential to remove the toxicity of ash before disposal into landfills or reutilization. Environmental characteristic analysis of BMW ash showed increased hardness (1320 mg/L) and chloride (8500 mg/L) content in leachate compared to World Health Organization (WHO) and Environment Protection Agency (EPA) guidelines for drinking water (hardness, 300 mg/L; chloride, 250 mg/L). The alkalinity and pH of the ash leachate were 400 mg/L and 8.35, respectively. In this paper, study was carried out to investigate the metal tolerance level of bacterial isolates isolated from soil. The isolate Bacillus sp. KGMDI can tolerate up to 75 mg/L of metal concentration (Mn, Mo, Cr, Fe, Cu, and Zn) in enriched growth medium. This shows that the isolated culture is capable of growing in presence of high concentration of heavy metals and acts as potential biological tool to reduce the negative impact of BMW ash on the environment during landfilling.